Outlining the Scope for Public Sector Involvement in Mental Health - Beeharry, Girindre; Whiteford, Harvey; Chambers, David; Baingana, Florence (World Bank, Washington, DC, 2013)
The paper documents the large and increasingly important contribution made by mental disorders to the global burden of disease. Disease burden does not provide sufficient justification for public intervention (understood as financing, provision, mandates, regulation or information) in the field of mental health. While there exists cost-effective interventions for some mental health disorders, the existence of such interventions, on their own, does not provide a sufficient basis for public intervention. The popular burden of disease and cost-effectiveness arguments therefore provide a weak foundation upon which to build a case for public intervention - and, a fortiori, for World Bank support to such intervention - in the field of mental health. This paper applies an algorithm for decision-making borrowed from Musgrove (1999) that orders the main criteria for public intervention to the field of mental health. The locus for reform efforts in the field is defined by the gap between the existing and the desirable features of mental health financing and provision.